Sound, body and space: audience experience in late medieval English drama - Wright, Clare (2011)
This thesis offers a new approach to the study of actor-audience relations in late medieval English drama and endeavours not only to emphasise the performative elements of medieval plays, but also the effects that they may have produced in performance. Adopting a phenomenological perspective, the work focuses on the audience's corporeal experience of the drama and draws on modern theories of performance, including the intersections with anthropology and, more recently, cognitive neuroscience. The literary, poetic and dramatic aspects of the three case studies chosen are analysed in depth with supporting evidence from the literature, iconography and theory of the period. Five distinct chapters divide the thesis: the first is an overview of the broader context of the study and the methodology used; Chapter Five discusses the findings and implications of the work, and the three central chapters each consider one key element in an audience's experience of medieval performance. Therefore, Chapter Two examines vocal sound in Christ before Herod; Chapter Three investigates the effects produced by the actor's physical movements in The Castle of Perseverance, while Chapter Four shifts attention onto the audience's activities in The Play of the Sacrament and how they may have contributed to the dramatic event. The findings suggest that, in many cases, medieval playwrights and performers had a sophisticated grasp of their medium, understanding its unique impact on human physiology and psychology and, moreover, that they consciously manipulated the fundamental components of the drama to create an experientially profound encounter for their audiences. These conclusions further highlight the need to re-evaluate current concepts of medieval performance space, as well as the extent to which the play texts themselves can illuminate the more ephemeral qualities of medieval theatre. But perhaps the most significant outcome of this thesis is the acknowledgement that medieval audiences not only read and heard what was presented to them, but felt the performances in both body and soul.